2016
DOI: 10.1128/jvi.02608-15
|View full text |Cite
|
Sign up to set email alerts
|

Human MicroRNA miR-532-5p Exhibits Antiviral Activity against West Nile Virus via Suppression of Host Genes SESTD1 and TAB3 Required for Virus Replication

Abstract: West Nile virus (WNV) is a mosquito-transmitted flavivirus that naturally circulates between mosquitos and birds but can also infect humans, causing severe neurological disease. The early host response to WNV infection in vertebrates primarily relies on the type I interferon pathway; however, recent studies suggest that microRNAs (miRNAs) may also play a notable role. In this study, we assessed the role of host miRNAs in response to WNV infection in human cells. We employed small RNA sequencing (RNA-seq) analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 69 publications
1
49
0
Order By: Relevance
“…These observed changes in miRNA expression may represent an arm of the host response to viral infection or manipulation of endogenous host cell pathways by the virus in order to promote a cellular environment more conducive to viral replication. In agreement with this possibility, multiple studies have identified miRNAs that inhibit the replication of various viruses (15,(18)(19)(20)(21). In contrast, cells lacking miRNAs due to the genetic ablation of Dicer have been shown to support the replication of several RNA viruses at levels equivalent to those in control cells with an intact miRNA population.…”
mentioning
confidence: 70%
“…These observed changes in miRNA expression may represent an arm of the host response to viral infection or manipulation of endogenous host cell pathways by the virus in order to promote a cellular environment more conducive to viral replication. In agreement with this possibility, multiple studies have identified miRNAs that inhibit the replication of various viruses (15,(18)(19)(20)(21). In contrast, cells lacking miRNAs due to the genetic ablation of Dicer have been shown to support the replication of several RNA viruses at levels equivalent to those in control cells with an intact miRNA population.…”
mentioning
confidence: 70%
“…Host miR-532-5p targets SEC14 and spectrin domains 1 and transforming growth factor ␤-activated kinase 1 (TAK1)-binding protein 3, thereby inhibiting West Nile virus replication (17). During influenza virus infection, host miR-485 not only regulates the expression of host genes but also targets the influenza virus gene to inhibit virus replication (18).…”
mentioning
confidence: 99%
“…Conversely, the viral induced degradation of host miRNA leads to block the cleavage of viral genome and viral protein. Second, changes in host miRNA expression could also lead to enhance antiviral effector resulting in reducing viral replication (54, 61). However, some viral infections mediate degradation of host miRNAs leading to downstream changes in host transcriptome that can be benefit virus replication and pathogenicity (4).…”
Section: Discussionmentioning
confidence: 99%